Callings Readers Guide - K-State First (My University, 2026)
This guide provides resources for using the Kansas State University 2026 common book, “Callings: The Purpose and Passion of Work” by David Isay and Maya Millett. Included in the guide are discussion questions, suggested classroom activities, and additional resources.
Keywords: Common reading program; Guide; First-year experience program; Application of learning